Influence of dietary conjugated linoleic acid (CLA) and tetradecylthioacetic acid (TTA) on growth, lipid composition and key enzymes of fatty acid oxidation in liver and muscle of Atlantic cod (Gadus morhua L.) - Kennedy, Sean Robert; Bickerdike, Ralph; Berge, Rolf K; Porter, Allan R; Tocher, Douglas R (Aquaculture, 2007)
The aim of the present study was to determine the effects of conjugated linoleic acid (CLA) and tetradecylthioacetic acid (TTA) on growth performance, and lipid and fatty acid metabolism in Atlantic cod. The overall objective being to test the hypotheses that CLA and TTA have beneficial effects in cod culture including decreased liver size and proportion through decreased lipid content, and increased nutritional quality through effects on fatty acid compositions including accumulation of bioactive fatty acids, CLA and TTA, in flesh. Juvenile cod were fed for three months on fish meal and fish oil diets of basically commercial formulation, but containing either 0.5% or 1% CLA, or 0.5% TTA. The effects of the functional fatty acids on growth, feed efficiency, body proximate composition, liver weight and lipid composition, fatty acid compositions of flesh and liver, and key enzymes of fatty acid oxidation were determined. Dietary CLA and TTA had no effect on growth parameters in cod juveniles, but viscero- and hepato-somatic indices were increased in fish fed 0.5% CLA and TTA, respectively. Proximate composition of whole fish was not affected by CLA or TTA, and there were no major effects of either functional fatty acid on lipid contents and compositions of liver and flesh. Dietary CLA and TTA were both incorporated into tissue lipids, with CLA deposited to a greater extent in liver, whereas TTA was deposited to a greater extent in flesh. In liver, acyl CoA oxidase (ACO) activity, but not carnitine palmitoyltransferase-I (CPT-I), was increased by CLA, whereas dietary TTA increased both ACO and CPT-I activities. In contrast, ACO activity was reduced by both CLA and TTA in red and white muscle, whereas CPT-I activity was generally not affected by CLA and TTA in either muscle tissue. Therefore, the results only partially supported the hypotheses tested, as CLA and TTA had few beneficial effects in Atlantic cod and did not enhance growth parameters, or improve feed conversion or potential yield through decreased ...